IMPLEMENTASI EDUGAME BERBASIS ROBLOX SEBAGAI METODE PEMBELAJARAN INOVATIF DI ERA DIGITAL 4.0: STUDI NARATIF DI SD NEGERI PASARBATANG 03 - Nisriina Amiirah Faatin; Markhamah; Ambarwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to apply learning methods in this modern era. Rapid technological developments have created a multitude of new developments, one of which is most relevant to today's lives. In this digital age, technology plays a significant role, not only for adults but also for children. Therefore, to provide a platform for children, who sometimes cannot yet distinguish between the positive and negative impacts of technological developments, close attention must be paid to the consumption period of gadgets and the choice of applications available on them. Focusing on this, many educational programs now also focus on learning experiences through gaming applications. The presence of technology not only facilitates access to information but also opens up new opportunities in learning methods. For the younger generation, especially students, technology has evolved into more than just a means of entertainment. Now, technology has become an interactive and engaging learning tool, motivating them to be more enthusiastic about exploring knowledge. In the context of language education, technology plays a crucial role in supporting the development of digital literacy, increasingly needed in the era of the Fourth Industrial Revolution. The use of games in education (Game-Based Learning or GBL) in 2025 is recognized as an effective method for creating active, interactive, engaging, and immersive learning experiences. One gaming platform that is very well-known and popular among children, teenagers, and perhaps even adults today is ROBLOX. Where in the game there are countless maps or game options that are fun and interesting and many there are also new learning tools. Roblox can be an effective educational tool because it hones creativity, logic, teamwork, and digital skills. Through game creation in Roblox Studio using the basic programming language Lua, and teaches subjects such as language, science, mathematics, and history interactively, although guidance is still needed to prevent addiction and ensure the educational content is age-appropriate for users. Because it is possible that in ROBLOX games there may still be some games that may not be age-appropriate for users and the impact of addiction to their use. Therefore, it is not only accepting and using, but also ensuring that what is currently developing can also be beneficial.